Relationship between Knowledge and Fatigue with Unsafe Behavior in Classification Workers - Juswan Sade (Collaborate, 2023)
A work accident is an unwanted and unexpected event caused by unplanned factors. One of the factors causing work accidents is personal factors, which include a lack of knowledge, expertise, and motivation, as well as physical and mental problems. Based on the results of previous studies, unsafe behaviour is one of the main causes of work accidents. Therefore, it is necessary to research to determine the relationship between personal factors such as knowledge, skills, and fatigue with unsafe behaviour in welding workers. The purpose of this study is to identify the relationship between personal factors and unsafe behaviour in welding workers in order to find appropriate preventive methods to minimize the occurrence of unsafe practices and work accidents. The results showed a significant relationship between knowledge and unsafe behaviour, with a significance value of 0.001. The correlation coefficient between knowledge and unsafe behaviour is -0.547, which indicates a strong relationship.